1988
DOI: 10.1111/j.1440-1827.1988.tb02334.x
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularization of Pericellular Fibrosis in Alcoholic Liver Disease

Abstract: The relationship between sinusoidal capillarization and pericellular fibrosis was studied in 29 specimens of human liver from patients with alcoholic liver disease. Immunohistochemically, factor VIII-related antigen was not observed in the normal sinusoidal lining cells, but was localized in the capillaries which proliferated in the pericellular fibrotic region. Fibronectin was localized in the proliferated endoplasmic reticulum of newly formed vascular endothelial cells and hepatocytes with the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…LYVE-1 expression in SECs was attenuated in hepatitis/ cirrhosis in association with sinusoidal capillarization, which is generally considered to be a cirrhosis-related vascular change [7][8][9]. Hyaluronan, a ligand of LYVE-1, is mostly degraded in hepatic SECs, and is elevated in the sera of patients with advanced liver fibrosis as a consequence of SEC dysfunction related to sinusoidal capillarization [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LYVE-1 expression in SECs was attenuated in hepatitis/ cirrhosis in association with sinusoidal capillarization, which is generally considered to be a cirrhosis-related vascular change [7][8][9]. Hyaluronan, a ligand of LYVE-1, is mostly degraded in hepatic SECs, and is elevated in the sera of patients with advanced liver fibrosis as a consequence of SEC dysfunction related to sinusoidal capillarization [23].…”
Section: Discussionmentioning
confidence: 99%
“…Expression patterns of molecular markers are also different between SECs and common vascular endothelium [4][5][6]. In normal livers, SECs rarely express von Willebrand factor (vWf), which is generally recognized as a reliable marker of vascular endothelial cells [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Такие области часто содержали отдель-но идущие артерии и расширенные синусоиды, сви-детельствующие, по-видимому, о наличии артерио-венозных шунтов. Синусоиды, выстланные CD34-положительными эндотелиальными клетками, могут быть эквивалентны «капилляризации», как описано Шаффнером, Поппером и другими [18,22] и сохра-няться при уменьшении активности миофибробла-стов (рисунок 6а).…”
Section: Discussionunclassified
“…In a case of chronic active hepatitis, many mesenchymal cells and hepatocytes in creased in the cirrhotic human liver (13). In vitro studies have suggested that hepatocytes can produce collagens (7, 14), and play an important role in fibrogenesis and neovascularization in pathological liver (18). However, type III collagen was not detected in the cytoplasm of hepatocytes.…”
Section: Frozen Sectionsmentioning
confidence: 99%